Predictors of Group Treatment Outcomes for Child Sexual Abuse: An Investigation of the Role of Demographic and Abuse Characteristics. (20th October 2014) - Hiller, Atara; Springer, Craig; Misurell, Justin; Kranzler, Amy; Rizvi, Shireen
Abstract : Research has begun to identify factors that may moderate the effects of interventions for symptomatology associated with child sexual abuse (CSA). However, there is disagreement about which factors may be important for different populations. The present investigation examined predictors of treatment outcomes among 166 predominantly economically disadvantaged and culturally diverse CSA survivors between the ages of six and ten, who were treated using game‐based cognitive‐behavioural therapy (GB‐CBT). Predictor variables included demographic characteristics (i.e. age, gender, ethnicity, household income) and abuse‐related risk factors (i.e. degree of invasiveness of abuse, frequency of instances of CSA and type of relationship to the perpetrator). Treatment outcomes included internalising and externalising symptoms, sexually inappropriate behaviours, knowledge of abuse and personal safety skills. Results indicate that participants' responsiveness to treatment was not impacted by demographic or abuse‐related risk factors. Thus, group treatment appears to be effective for treating a wide range of problems following CSA, irrespective of clients' varied demographic background and abuse characteristics. Copyright © 2014 John Wiley & Sons, Ltd. '166 predominantly economically disadvantaged and culturally diverse CSA survivors between the ages of six and ten' Key Practitioner Messages: GB‐CBT is an integrative treatment approach for survivors of CSA, combining features of trauma‐focused cognitive‐behavioural therapy (TF‐CBT), play therapy and group therapy. It is important to investigate whether demographic and abuse characteristics impact treatment outcomes for CSA to determine whether children respond differently to treatment based on pre‐existing characteristics. GB‐CBT participants experienced improvements in internalising and externalising symptoms, sexually inappropriate behaviours and personal safety skills, irrespective of their demographic backgrounds and varied abuse histories. 'GB‐CBT is an integrative treatment approach for survivors of CSA'